Faktor Yang Berhubungan Dengan Perilaku Safety RidingPada Mahasiswa Kesehatan Masyarakat SebagaiPengendara Sepeda Motor - Aeni, Qurotul; , Kusuma Estu Werdani, SKM., M.Kes (2016)
Pioner promotion of health as the students public health contribute by behavior is safe in motorcycles. It is evident that there is still a student public health is unable to make efforts to prevent an accident drive. One effort that can be taken to prevent the occurrence of accidents is by implementing secure behavior in driving motorcycles (safety riding). This research aims to know the factors related to the behavior of safety public health student riding at Muhammadiyah University of Surakarta. This type of research is observational, with cross sectional approach. Sample research as much as 161 people out of a total population of 256 public health students who rode motorcycles. The independent variable in this study is the knowledge, experience and attitude, while the dependent variable in this study is behavior safety riding. The results of the research analysis using Chi-Square test shows that there is no relationship between knowledge and attitudes with behavioral safety riding (p = 0,903 and p = 0,402), but there is a relationship between experience with behavioral safety riding (p = 0,004).